Literasi Keuangan dan Sikap Keuangan Dalam Membentuk Financial Behavior - Nurjannah Nurjannah; Andi Tenri Ampa; Hikmayani Subur (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The purpose of this study is to investigate the connection between students' financial behavior or financial behavior and financial literacy and attitudes. Monetary proficiency alludes to's how understudies might interpret ideas and information connected with individual budget, while monetary perspectives mirror understudies' psychological and close to home mentalities towards cash, monetary administration and speculation. Adult students from a variety of social and economic backgrounds are asked to respond to a survey as part of this research method. The survey has questions about financial behavior, attitudes toward money, and financial literacy. The collected data were then analyzed using statistical techniques and SPSS to determine whether or not the variables of financial literacy, financial attitudes, and financial behavior were linked together. According to the findings of this study, financial literacy and attitudes toward prudent financial behavior are positively correlated. Students who have a high level of financial literacy are more likely to have positive financial attitudes, which in turn influence them to make better financial decisions and manage their personal finances more effectively. On the other hand, students who lack financial literacy or have negative financial attitudes are more likely to engage in poor financial behavior like overspending, not saving enough, and managing their debt in an unhealthy way.